Amperometric glucose biosensor with the IrNPs/Ludox – modified enzyme matrix - Shkotova, L.V.; Woloshina, I.M.; Kovalchuk, V.V.; Zhybak, M.T.; Dzyadevych, S.V. (Вiopolymers and Cell, 2018)
Aim. To develop an amperometric biosensor based on glucose oxidase (1.1.3.4) from Aspergillus niger immobilized in the IrNPs/Ludox/GOx matrix for glucose detection. Methods. To achieve a highly selective and sensitive glucose detection, the enzymatic membrane was functionalized with Ir nanoparticles (IrNPs) and silica composite Ludox. The enzymatic selective layer was formed on the surface of a platinum disk electrode using immobilization in glutaraldehyde vapor. Results. The voltamperometric characteristics of the transducers with modified IrNPs/Ludox/GOx matrix were studied. Enzyme immobilization on the surface of amperometric transducers was optimized to perform sample analysis. Modified transducers improved biosensor sensitivity. The analytical characteristics of amperometric transducer were determined: detection limit is 0.1 µM (s/n = 3), linear working range is 0.05–3.2 mM, sensitivity is 106 mA×M⁻¹×cm⁻². Conclusions. Application of the matrix modified with Ir nanoparticles and silica composite Ludox was investigated for the amperometric glucose biosensor as the most studied model of biosensors. A significant increase in the biosensor sensitivity was obtained using the new approach of glucose oxidase immobilization; therefore application of the matrix modified with mesoporous silica composite and nanometals opens new possibilities to obtain a bioselective membrane of high sensitivity and stability at the development of new electrochemical biosensors.